Effect of Integrated Management of Biological and Chemical Nitrogen Fertilizers with Different Plant Densities on Seed and Oil Percentage of Sunflower (Helianthus annuus L.) under Water Deficit Stress - Hassan Rahmani; Mani Mojaddam; Alireza Shokuhfar; Mojtaba Alavi Fazel; Shahram Lak (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
This experiment was carried out in split plots based on randomized complete block design with three replications during 2015-2016 and 2016-2017 cropping years in Khuzestan province. The main factor, consisted as water shortage stress with four levels of irrigation after depletion of 45, 60, 75 and 90% of plant usable water was optimal irrigation, mild stress, severe stress and very severe stress, respectively. The levels of 100% chemical fertilizer, 75% and 50% combination of chemical fertilizer with 100% nitroxin and plant density at three levels of 57, 71 and 95 thousand plants per hectare were as sub-factors. The results showed that the interaction of water shortage stress, combination of nitrogen biochemical and chemical fertilizer and plant density had a significant effect on grain yield, 1000-grain weight, number of seeds per head, harvest index and biological yield. The highest seed yield was obtained from the optimal irrigation treatment by combining 75% of chemical and biological fertilizers and a density of 95,000 plants per hectare, which showed a 75% increase compared to the very severe moisture stress treatment with 75% of chemical and biological fertilizers and a density of 57,000 plants per hectare. The interaction of moisture stress and density and fertilizers on oil percentage and leaf area index was significant. In general, the use of nitrogen from both chemical and biological sources at a density of 95,000 plants per hectare may reduce the effects of moisture stress on the sunflower plant in the experimental condition.